Illocutionary Acts in Iconic Musicals: A Pragmatic Study of Jesus Christ Superstar and Les Miserables - Kusuma, Marsya Purnanditha; Baron, Rifari; Nurjanah, Nurjanah (Universitas Indraprasta PGRI, 2024)
This study aims to determine: 1) The social and contextual aspects of each story influencing the illocutionary behaviors in Les Misables and Jesus Christ Superstar, 2) The kinds of conversational implicature and politeness methods do the characters in Les Misables and Jesus Christ Superstar use to negotiate power dynamics and interpersonal problems, and 3) The pragmatic force of illocutionary acts strengthened in the dialogue of Jesus Christ Superstar and Les Misables. The research approach used is qualitative descriptive. The research subjects are the drama scripts. The findings of this study reveal that there is a significant difference between Judas and Valjean illocutionary acts that lead to distinctive the social and contextual aspect. Moreover, there is a pivotal similarity between Judas and Valjean to navigate the power dynamics and interpersonal conflicts. At last, there is a pragmatic force between Judas Iscariot and Jean Valjean to communicate complex emotional and social dynamics.